Sosialisasi Penggunaan Aplikasi Canva sebagai Media Pembelajaran dan Sarana Pengembangan Kreativitas Siswa di Sekolah SMK Muhammadiyah 3 Terpadu Pekanbaru - Rini Hardiyanti Ali; Vingky Zulfa Asria; Lica Perta Juliyas Muharni; Sahrul; Novita Sari (LPPI UMN AL WASHLIYAH, 2026)
His community service activity aims to enhance the use of digital technology in the learning process through the socialization of Canva application as a learning medium and a tool for developing students' creativity at SMK Muhammadiyah 3 Terpadu Pekanbaru. The background of this activity is based on the low level of students’ understanding and utilization of Canva as an innovative and interactive learning medium.The results showed an increase in students’ understanding by 45%, creativity by 43%, and learning motivation by 40%. Therefore, Canva is effective in supporting innovative and interactive learning.The expected outcomes of this activity are an increase in students’ knowledge and skills in using Canva as a learning medium, along with the growth of students’ creativity in presenting learning materials in an engaging and interactive way. Therefore, this activity is expected to support the creation of a more effective, innovative, and meaningful learning process in the digital era.